FAKTOR-FAKTOR YANG MEMPENGARUHI PERUBAHAN PERILAKU PASIEN HIV/AIDS - Nur’ Ainun Jambak; Aria Wahyuni (Jurnal Ilmiah Keperawatan, 2018)
Treatment of HIV/AIDS can be given by medical and supported by behavioral changes. This study aims to determine the factors that influence behavior change in patients with HIV/AIDS. Design of the research is descriptive analytic with cross sectional study. This research was conducted in a clinic HIV/AIDS of a hospital in Bukittinggi West Sumatera. The population of this study is that patients with HIV / AIDS who actively visiting the clinic HIV / AIDS amounted to 98 people. he sample taken by purposive sampling as many as 82 people with the criteria of patients willing to be sampled. The data were analyzed using univariate and bivariate analysis (Chi-Square Test).The result showed most respondents have a high knowledge (61%), high motivation (57.3%), good family support (51.2%), counseling is high (59.8%) and behavioral changes in a positive direction (52 , 4%). Statistical analysis showed the relationship between knowledge (p = 0.005; OR = 7), motivation (p = 0.005; OR = 9.84), family support (p = 0.005; OR = 6.57) and counseling HIV / AIDS ( p = 0.005; OR = 7.81) with the change in the behavior of patients with HIV / AIDS. It can be concluded there is a relation between knowledge, motivation, counseling and family support behavior change HIV / AIDS patients.Expected at the hospital and the respondent is always active giving and receiving counseling in order to reduce the incidence of HIV / AIDS and is expected to families receiving family members of HIV / AIDS. The next research is done with different variables such as perception, emotion, age, peer support.